Respuesta :

Answer:

− 9/2

Step-by-step explanation:

Let's solve your equation step-by-step.

4(x−6)+6=6x−9

Step 1: Simplify both sides of the equation.

4(x−6)+6=6x−9

(4)(x)+(4)(−6)+6=6x+−9(Distribute)

4x+−24+6=6x+−9

(4x)+(−24+6)=6x−9(Combine Like Terms)

4x+−18=6x−9

4x−18=6x−9

Step 2: Subtract 6x from both sides.

4x−18−6x=6x−9−6x

−2x−18=−9

Step 3: Add 18 to both sides.

−2x−18+18=−9+18

−2x=9

Step 4: Divide both sides by -2.

−2x/−2=9/−2

x=−9/2

r3t40

Ah cute.

We have the following equality

[tex]4(x-6)+6=6x-9[/tex].

First we will distribute the parentheses on the left side to get

[tex]4x-24+6=6x-9[/tex].

Then move x-terms to left side and other terms to right side

[tex]-2x=9[/tex].

Finally divide both sides of equation by -2 to get

[tex]x=\boxed{-\dfrac{9}{2}}[/tex].

Hope this helps.